Labeling human melanoma cells with SPIO: in vitro observations - Spira, Daniel (Molecular imaging, 2016)
Objectives: To use the superparamagnetic iron oxide (SPIO) contrast agent Resovist (±transfection agent) to label human melanoma cells and determine its effects...
Gesehen am 12.05.2020